The Taming of Psidium guajava: Natural and Cultural History of a Neotropical Fruit - Arévalo-Marín, Edna; Casas, Alejandro; Landrum, Leslie; Shock, Myrtle P.; Alvarado-Sizzo, Hernán; Ruiz-Sanchez, Eduardo; Clement, Charles R. (Frontiers in Plant Science, 2021)
Guava (Psidium guajava L., Myrtaceae) is a Neotropical fruit that is widely consumed around the world. However, its evolutionary history and domestication process are unknown. Here we examine available ecological, taxonomic, genetic, archaeological, and historical evidence about guava. Guava needs full sunlight, warm temperatures, and well-distributed rainfall throughout the year to grow, but tolerates drought. Zoochory and anthropochory are the main forms of dispersal. Guava's phylogenetic relationships with other species of the genus Psidium are unclear. A group of six species that share several morphological characteristics are tentatively accepted as the Psidium guajava complex. DNA analyses are limited to the characterization of crop genetic diversity within localities and do not account for possible evolutionary and domestication scenarios. A significant amount of archaeological information exists, with a greater number and older records in South America than is Mesoamerica, where there are also numerous historical records. From this information, we propose that: 1) the guava ancestor may have originated during the Middle or Late Miocene, and the savannas and semi-deciduous forests of South America formed during the Late Pleistocene would have been the most appropriate ecosystems for its growth, 2) the megafauna were important dispersers for guava, 3) dispersal by humans during the Holocene expanded guava’s geographic range, including to the southwestern Amazonian lowlands, 4) where its domestication may have started, and 5) with the European conquest of the Neotropics, accompanied by their domestic animals, new contact routes between previously remote guava populations were established. These proposals could direct future research on the evolutionary and domestication process of guava.